Medication Persistence to Lipid-lowering Agents As Cost-saving Opportunities in Indonesian Patients with Acute Coronary Syndrome after Percutaneous Coronary Intervention - Kristin, Erna ([Yogyakarta] : Universitas Gadjah Mada, 2022)
Medication persistence is known to reduce acute coronary syndrome (ACS) disease mortality. As much as 13% of Indonesia's budget on national health insurance programs was used for cardiovascular disease. The number of population-based studies discussing the cost-saving opportunities of medication persistence in ACS patients undergoing percutaneous coronary syndrome (PCI) is still minimal. This study aimed to investigate the estimated cost saving of persistence to lipid-lowering agents in patients with ACS after their first PCI. Hospital-based, retrospective cohort study with 2 years of follow-up was conducted with 367 patients. Patients were deemed as having medication persistence if the gap between prescriptions was ≤ 30 days. Persistence assessment was done for lipid-modifying agents (WHO ATC Code: C10). The main outcome is cost-saving opportunities assessed by dividing the difference in total costs resulting from medication persistence with the difference in the proportion of major adverse cardiovascular events (MACE) and major adverse cardiovascular and cerebrovascular events (MACCE) prevented by medication persistence. The study found that direct medical costs incurred by persistent patients were significantly lower than non-persistent patients with lipid-lowering agents (IDR 9,535,209.76 versus IDR 15,933,959.28). Persistence to lipid-lowering therapy can prevent one MACE incident with cost-saving of IDR 996,192.41 when compared to non-persistence patients, while one MACCE incident can be prevented with cost-saving of IDR 733,103.02. Our study indicates that among ACS patients who underwent their first PCI, medication persistence with lipid-lowering agents can contribute to cost-saving in preventing one MACE or MACCE event. These data will be useful for policymakers to help budget allocation and reemphasize the important role of medication persistence with lipid-lowering therapy in the management of ACS after PCI.